The Routledge History of Emotions in Europe 1100-1700 - Lynch, Andrew; Broomhall, Susan (Taylor & Francis, 2020)
The Routledge History of Emotions in Europe: 1100-1700 presents the state of the field of pre-modern emotions during this period, placing particular emphasis on theoretical and methodological aspects of current research. This book serves as a reference to existing research practices in emotions history and advances studies in the field across a range of scholarly approaches. It brings together the work of recognized experts and new voices, and represents a wide range of international and interdisciplinary perspectives from different schools of research practice, including art history, literature and culture, philosophy, linguistics, archaeology and music. Throughout the book, central and recurrent themes in emotional culture within medieval and early modern Europe are highlighted from different angles, and each chapter pays specialist attention to illustrative examples showing theory and method in application. Exploring topics such as love, war, sex and sexuality, death, time, the body and the family in the context of emotional culture, The Routledge History of Emotions in Europe: 1100-1700 reflects the sharp rise in scholarship relating to the history of emotions in recent years and is an essential resource for students and researchers of the history of pre-modern emotions.